2017
DOI: 10.1038/nature24281
|View full text |Cite
|
Sign up to set email alerts
|

Two independent modes of chromatin organization revealed by cohesin removal

Abstract: Imaging and chromosome conformation capture studies have revealed several layers of chromosome organization, including segregation into megabase-large active and inactive compartments, and partitioning into sub-megabase domains (TADs). Yet, it remains unclear how these layers of organization form, interact with one another and impact genome functions. Here, we show that deletion of the cohesin-loading factor Nipbl, in mouse liver, leads to a dramatic reorganization of chromosomal folding. TADs and associated p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

124
1,185
7
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 1,054 publications
(1,318 citation statements)
references
References 73 publications
124
1,185
7
2
Order By: Relevance
“…Given that cohesin binding is implicated in sister chromatid cohesion and gene expression (Merkenschlager, 2010; Merkenschlager and Odom, 2013), ultraconservation within NIPBL may speak to this gene’s importance in genome structure and function. Indeed, a recent study demonstrated that depletion of NIPBL in mouse affects reorganization of chromosome folding (Schwarzer et al, 2017). Furthermore, the evolutionarily conserved position of the NIPBL gene within boundaries may suggest that the lack of three-dimensional associations across a boundary may also be important for its expression.…”
Section: Discussionmentioning
confidence: 99%
“…Given that cohesin binding is implicated in sister chromatid cohesion and gene expression (Merkenschlager, 2010; Merkenschlager and Odom, 2013), ultraconservation within NIPBL may speak to this gene’s importance in genome structure and function. Indeed, a recent study demonstrated that depletion of NIPBL in mouse affects reorganization of chromosome folding (Schwarzer et al, 2017). Furthermore, the evolutionarily conserved position of the NIPBL gene within boundaries may suggest that the lack of three-dimensional associations across a boundary may also be important for its expression.…”
Section: Discussionmentioning
confidence: 99%
“…These DNA regions are enriched in bound CTCF and cohesin subunits, suggesting architectural constraints such as helping to either trigger or prevent interactions between promoters and enhancers (Kagey et al 2010;Sofueva et al 2013;Zuin et al 2014). They were shown to function in the constitutive organization of TADs (Dixon et al 2012;Phillips-Cremins et al 2013;Rao et al 2014), since removal of either CTCF or the cohesin complex affects TAD stability (Haarhuis et al 2017;Nora et al 2017;Rao et al 2017;Schwarzer et al 2017). In the case of HoxD, the TAD border can be mapped in the "posterior" part of the cluster, between Hoxd11 and Hoxd12; i.e., in a genomic region showing one of the highest GC contents genome-wide and displaying nine bound CTCF sites within a 40-kb region (Soshnikova et al 2010) as well as close to 10 active promoters.…”
Section: Initially the Telomeric Tad (T-dom) Located Inmentioning
confidence: 99%
“…These technologies provided critical insights into key structural and functional components of three-dimensional chromatin organization such as i) A/B compartments (Lieberman-aiden et al 2009), also referred to as compartment domains (Rao et al 2017), which are closely associated with open and closed chromatin domains, respectively; ii) topologically associating domains (TADs) (Dixon et al 2012;Nora et al 2012;Sexton et al 2012), also referred to as contact domains (Rao et al 2017), chromosomal units that spatially constrain cis-regulatory interactions; iii) CTCF loops, also referred to as insulated neighborhoods (Hnisz et al 2016) or loop domains (Rao et al 2017). Interestingly, while these studies suggested a hierarchical domain organization, recent studies based on acute depletion of CTCF or cohesin, or inactivation of the cohesin-loading factor NIPBL, demonstrated that A/B compartments and TADs are not hierarchically organized but represent independent structural (and possibly functional) units of 3D genome organization (Nora et al 2017;Rao et al 2017;Wutz et al 2017;Schwarzer et al 2017). …”
Section: Introductionmentioning
confidence: 99%